The Sweet Taste of Honors… and Money. Business and Titled Nobility in Cuba (1700-1833) - Ramón MARURI VILLANUEVA (Cuadernos Dieciochistas)
In Cuba, the process of formation of the titled nobility begins in the early eighteenth century, extending until the late nineteenth. This study covers chronologically until 1833, the year that marks the end of the Old Regime in the Spanish Monarchy. Its objective has been raised from a double dimension; one, to know the business world in which the forty-four natives or neighbors of Cuba moved, who, coming from it, itentered into the ranks of the titled nobility between 1700 and 1833; the other dimension is to give an account of the merits and services for which the Monarchy distinguished them with the maximum expression of social notability, as it was a noble title.